Tailored pore size and microporosity of covalent organic framework (COF) membranes for improved molecular separation - Digambar B. Shinde; Li Cao; Xiaowei Liu; Dinga A.D. Wonanke; Zongyao Zhou; Mohamed N. Hedhili; Matthew Addicoat; Kuo-Wei Huang; Zhiping Lai (Journal of Membrane Science Letters, 2021)
Three crystalline truxene-based β-ketoenamine COF membranes (TFP-HETTA, TFP-HBTTA and TFP-HHTTA) are fabricated via a de novo monomer design approach to understand the fundamental correlations between pore structure and molecular separation performance. By introducing bulky alkyl groups into the truxene framework, the pore size of TFP-HETTA, TFP-HBTTA, and TFP-HHTTA are systematically tuned from 1.08 to 0.72 nm. Accordingly, the TFP-HETTA showed good water permeance of 47 L m−2 h−1 bar−1 along with a prominent rejection rate of Reactive Blue (RB, 800 Da) but less than 10% rejection rate of inorganic salts. In contrast, the TFP-HHTTA membrane with pore size of 0.72 nm can reject small dye molecules such as Safranin O (SO, 350 Da) and trivalent salts but with a moderate water permeance of 19 L m−2 h−1 bar−1. The pore-flow model rooted from the viscous flow could well fit the observed organic solvent nanofiltration results of all three COF membranes.